The Influence of Ethical Judgment on Whistleblowing Decision Making Mediated by Mood - Dharma Satria, Hengky; Rahmat, Adi; Yunefri, Yogi (Yayasan Education Al Aqsho Modern, 2023)
The aim of this research is to determine the influence of ethical judgment on whistleblowing decision making which is mediated by mood. The location of the research was carried out at PT. Pertamina Hulu Rokan with a sample size of 248 and consisting of 3 work areas. Data collection techniques use questionnaires and distributing questionnaires using Google Form. The data analysis technique in this research is Structural Equation Modelling (SEM) using SMArtPLS as a data processing tool. The results of this research show that ethical judgment has a positive and significant effect on whistleblowing decision making which is mediated by mood, so it is known that mood can mediate the relationship between ethical judgment and whistleblowing decision making. Apart from that, this research is also expected to contribute to the development of human resource management theory and practice, especially in increasing employee professionalism through these factors